Argument-driven inquiry in life science : lab investigations for grades 6-8 - Enderle, Patrick J., ....-; Bickel, Ruth, ....-; Gleim, Leeanne, ....- (Arlington : NSTA Press, 2015)
If you've been wanting to bring the benefits of argument-driven inquiry to your middle school life science classes, this book will help you get started. The book provides 20 field-tested labs to help your students learn how to read, write, speak, and use math in the context of science. These investigations are much more authentic than traditional laboratory activities because students both learn important content and participate in scientific practices. The students design their own method, develop models, collect and analyze data, and critique information. The labs cover topics in four broad areas of life science: molecules and organisms, ecosystems, biological evolution, and heredity. This new book follows the same winning formula as the high school versions of Argument-Driven Inquiry for Chemistry and Biology. Each easy-to-use lab includes reproducible student pages, teacher notes, and checkout questions. The labs are versatile enough to introduce a topic or to conclude the unit by having students apply what they've learned. Perhaps most important, the authors are veteran teachers like you. They know the importance of connecting all of the investigations to today's standards—and of providing the information and instructional materials you need in one useful resource that combines literacy, math, and science.
Keywords: Natuurwetenschappen -- Secundair onderwijs